Pengaruh Pajak, Intangible Assets, dan Mekanisme Bonus Terhadap Keputusan Transfer Pricing - Anggun Rizki Novira; Leny Suzan; Ardan Gani Asalam (Pusat P2M Politeknik Negeri Batam, 2020)
Transfer pricing is the price for the delivery of goods, services, or other intangible assets at related parties transact with each other based on the arm’s lenght principle. The purpose of this study to examine the influence factors of tax, intangible assets, and bonus mechanism on transfer pricing decisions. The population in this study are mining sector companies listed on the Indonesian Stock Exchange from 2015-2018. Sample selection technique used in purposive sampling and acquired 13 sample companies. The data used in this study was obtained from financial statement. Methods of data analysis in this research in logistic regression analysis using SPSS software version 23. The result showed that simultaneous tax, intangible assets, and bonus mechanism have a significant effect on transfer pricing decision. Tax partially have no significant effect on transfer pricing decision, while intangible assets has a significant positive effect on transfer pricing, and bonus mechanism have no significant effect on transfer pricing decision.